2016
DOI: 10.1021/acs.accounts.5b00538
|View full text |Cite
|
Sign up to set email alerts
|

Metalloprotein Crystallography: More than a Structure

Abstract: ConspectusMetal ions and metallocofactors play important roles in a broad range of biochemical reactions. Accordingly, it has been estimated that as much as 25–50% of the proteome uses transition metal ions to carry out a variety of essential functions. The metal ions incorporated within metalloproteins fulfill functional roles based on chemical properties, the diversity of which arises as transition metals can adopt different redox states and geometries, dictated by the identity of the metal and the protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 54 publications
(151 reference statements)
0
86
0
Order By: Relevance
“…Based on an established method to evaluate the elemental composition of materials, 31 this technique can be utilized to analyze the X-ray fluorescence of elements present in single-crystal samples and can be used in tandem with collecting diffraction data on the synchrotron beamline. 32 X-rays at a fixed incident energy are used to excite elements that emit photons corresponding their K-edge energies, with Compton backscattering observed near the incident energy. Fluorescence counts of various elements are detected, and emission spectra are calibrated to a standard containing Sm, Ni, Zn, Br, and Sr. Crystals were analyzed on 100-μm loops, and measurements for the sample (X-rays positioned on crystal, red lines in Figure 1) and a blank (X-rays positioned on an empty space of the loop, black lines in Figure 1) were taken at 0.9792 Å incident energy.…”
Section: Resultsmentioning
confidence: 99%
“…Based on an established method to evaluate the elemental composition of materials, 31 this technique can be utilized to analyze the X-ray fluorescence of elements present in single-crystal samples and can be used in tandem with collecting diffraction data on the synchrotron beamline. 32 X-rays at a fixed incident energy are used to excite elements that emit photons corresponding their K-edge energies, with Compton backscattering observed near the incident energy. Fluorescence counts of various elements are detected, and emission spectra are calibrated to a standard containing Sm, Ni, Zn, Br, and Sr. Crystals were analyzed on 100-μm loops, and measurements for the sample (X-rays positioned on crystal, red lines in Figure 1) and a blank (X-rays positioned on an empty space of the loop, black lines in Figure 1) were taken at 0.9792 Å incident energy.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the simultaneous measurement of many important parameters, XAS is among the best techniques for determining the "structure-to-function" relationship in metalloprotein studies. XAS structural studies of metal-binding sites from purified metalloproteins, which are often carried out jointly with X-ray crystallography, will not be considered in this review, information about this procedure can be found in other articles [14][15][16]. However, the emerging development of XAS in combination with chromatographic methods to characterize proteins from complex samples will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…A key benefit of [Fe–S] proteins for structure determination is that you may be able to use the Fe anomalous signal to solve the phase problem (Bowman, Bridwell-Rabb, & Drennan, 2016), provided you are careful to avoid loss of the damage-sensitive anomalous signal. The Fe anomalous absorption peak is at ~7112eV (1.7433Å ), which is accessible at most of synchrotron beamlines, such as SIBYLS at the Advanced Light Source (Classen et al, 2013).…”
Section: [Fe–s] Protein Crystallization Data Collection and Strumentioning
confidence: 99%
“…3). The proper refinement of [Fe–S] cluster structures may reveal the extend to which their distortion impacts enzymatic activity and biological function (Bowman et al, 2016). Such distortion can be further measured by Mossbauer spectroscopy (Pandelia, Lanz, Booker, & Krebs, 2015) and XAS (Einsle, Andrade, Dobbek, Meyer, & Rees, 2007; Ha et al, 2017) to evaluate the coordination geometry, solvation, and redox states of [Fe–S] clusters.…”
Section: [Fe–s] Protein Crystallization Data Collection and Strumentioning
confidence: 99%